History of the E.I. Martsinovsky Institute of Medical Parasitology and Tropical Medicine: research on malaria and leishmaniasis - Margarita V. Strelkova; Alla M. Baranova; Katrin Kuhls (História, Ciências, Saúde: Manguinhos)
Abstract This review presents the 100-year history of the Martsinovsky Institute of Medical Parasitology and Tropical Medicine in Moscow, Russia, starting with its foundation and early activities, and also describes the impact of its leading scientists, some of whom became internationally known. The institute headed a network of nine tropical institutes in the various Soviet republics from the 1920s to 1990. The extensive body of literature on the history and research accomplishments of this institute has mainly been published in Russian; our goal here is to introduce these achievements and this expertise to the international scientific and medical community, focusing on malaria and leishmaniasis and the development of measures to control and monitor these diseases in the USSR.